2023
DOI: 10.1088/1402-4896/acd6e2
|View full text |Cite
|
Sign up to set email alerts
|

The morphological and mechanical characterization of UHMWPE based composite: an experimental study

Abstract: Natural fiber and its hybrid composites have a promising future due to their economic, lightweight, environmentally superior, and sustainable properties. The purpose of this research is to explore the morphological and physical properties of composites made of hemp-epoxy and ultra-high molecular weight polyethylene-hemp-epoxy. The compression moulding technique is used to fabricate the UHMWPE -hemp hybrid composite and hemp-epoxy sample at a different orientation. These samples are subjected to different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…When reinforced into polymer matrices, these natural fibers generate composites with good mechanical characteristics, minimal weight, recyclability, and biodegradability. The features of natural fibers, such as good strength and stiffness, availability, and low cost, have increased their demand in industries such as automobiles, medicine, construction, and electronics [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…When reinforced into polymer matrices, these natural fibers generate composites with good mechanical characteristics, minimal weight, recyclability, and biodegradability. The features of natural fibers, such as good strength and stiffness, availability, and low cost, have increased their demand in industries such as automobiles, medicine, construction, and electronics [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, at high strain rates, the tensile strength and tensile modulus of the composites increased. Basrani et al [20,21] performed the tensile test on hybrid GFRP and hemp-UHMWPE composite at different strain rates using a servo hydraulic machine to study the strain rate effect. They found that tensile strength has been enhanced by 8.21% for hybrid GFRP and 56.46% for the hybrid hemp-UHMWPE as the strain rate increases.…”
Section: Introductionmentioning
confidence: 99%